PERHITUNGAN HARGA POKOK PRODUK DENGAN METODE FULL COSTING DAN VARIABLE COSTING UNTUK MENENTUKAN HARGA POKOK PROSES TERHADAP PERBANDINGAN LABA - Kristanti, Ika Neni (P4M STIE Putra Bangsa, 2015)
This study aims to determine the calculation of the cost of the process of knowing the comparison of profits in the calculation of the cost of the process between the full costing method and variable costing on SMEs